Model Pengelolaan Wakaf Produktif pada Masjid dan Pesantren Berbasiskan Hukum Islam dan Peraturan: Studi di Palembang - Kencana, Ulya; Gibtiah, Gibtiah (Universitas Batanghari Jambi, 2024)
Palembang, the oldest city in Indonesia, has historical religious assets. The mosque has a unique character, built in the 18th century, standing on the bank of the Musi River, founded by a famous charismatic ulama figure, as a waqf treasure and designated as a cultural heritage. The Islamic boarding school is considered the oldest, standing not far from the river with private ownership status. Both assets still exist today, are maintained and continue to develop. The aim of this research is to discover laws regarding regulations, as a basis for a productive waqf management model in developing mosques and Islamic boarding schools in Palembang with legal certainty. This study takes another side regarding the productive waqf management model. Through observations, interviews, and document studies, used to build an analysis as seen in this paper. The data is grouped and analyzed so as to provide a complete explanation of the problem. This study clearly shows a model for developing mosques with waqf status and Islamic boarding schools have private property status, both management models are conventional. Even though there is legal certainty with the Waqf Law, allows managing waqf productively. The findings show that there are no productive waqf management practices, even though there is already a desire for it. This is because the socialization of regulations has not been evenly distributed, This is because the socialization of regulations has not been evenly distributed,